Factors influencing exercise capacity in people with thoracic cancer. (1st April 2011) - Maddocks, M; England, R; Manderson, C; Wilcock, A
Abstract : Abstract: Introduction and aims: Patients with thoracic cancer often complain of a reduced exercise capacity which can impede levels of independence and quality of life. Several factors may be responsible but there is little formal study in this group. We have explored how various physiological and psychological factors relate to performance in a test of exercise capacity. Methods: Inspiratory muscle strength, peripheral muscle power, lung function and mastery over breathlessness were assessed using sniff nasal inspiratory pressure, leg extensor power, simple spirometry and the mastery domain of the Chronic Respiratory Disease Questionnaire respectively. Exercise capacity was assessed using the Incremental Shuttle walk Test (ISWT) during which patients wore a K4 b2 system allowing continuous measurement of heart rate, minute ventilation (VE) and oxygen uptake (VO2). Relationships between ISWT distance and independent factors were determined using Pearson's correlation coefficient and β regressions coefficients. Results: 41 patients (21 male, mean (SD) age 64 (8) years) took part. They walked a median (IQR) 320 (250–430) m and reached 76 (10)%, 48 (14)% and 77 (25)% of their predicted maximal heart rate, VE and VO2 respectively. Exercise capacity was significantly associated only with inspiratory muscle strength (r=0.42, p<0.01) and peripheral muscle power (r=0.39, p=0.01). These factors were also significant determinants of exercise capacity (β coefficients (95% CI) 1.77 (0.53 to 3.01) and 1.22 (0.31 to 2.14)). Conclusions: Both inspiratory and peripheral muscle performance appear to influence exercise capacity in people with thoracic cancer. Interventions aimed at maintaining or slowing down the decline in exercise capacity should include components targeting muscular performance.